Gestational Diabetes Mellitus and physical activity: exploring the issues among Asian population in the UK and advocating for policy change: a mixed-method study - Alaslani, Hadeel (2024)
Background and aim: Gestational Diabetes Mellitus (GDM), a glucose intolerance disorder resulting in hyperglycaemia, affects approximately one in every 23 pregnancies in the United Kingdom (UK). Compared to other ethnic groups in the UK, Asian-born women have a higher rate of GDM (5.8%).Physical activity is reported to have numerous benefits for both the expectant mother and foetus, such as improving insulin sensitivity and reducing the risk of developing GDM. This study examines the patterns of physical activity that impact GDM occurrence among Asian pregnant women living in the UK by: 1) assessing the association between patterns of physical activity engagement by Asian pregnant women and GDM occurrence; 2) gaining insight into Asian women’s knowledge of GDM and identifying barriers to and enablers of physical activity during pregnancy.